Comparison of the inhibitory activity of Moringa oleifera and Moringa peregrina extracts against two types of human pathogenic bacteria - abdullah hussein shalaal; F.h.R. Al-miahy (University of Thi-Qar Journal of agricultural research, 2025)
The study aimed to investigate the effect of the alcoholic extract of the leaves of two Moringa species on two types of bacteria, Gram-positive Staphylococcus aureus and Gram-negative Klebsiella pneumoniae, which are pathogenic to humans. The results of the analysis of the alcoholic extract of the leaves of two Moringa species indicated that the Moringa oleifera leaf extract had an inhibitory effect on the growth of Staph. aureus bacteria. All concentrations of the ethanolic extract of Moringa oleifera leaves had a significant inhibitory effect on the growth of Staph. aureus and the effect increase with the increase of the used concentration, as the diameter reached a maximum of 18.17 mm at a concentration of 100 mg ml-1. Moringa oleifera leaf extract did not have an inhibitory effect on the growth of Klebsiella pneumoniae bacteria at all extract concentrations. The results of the analysis of the alcoholic extract also showed that the Moringa peregrina leaf extract had an inhibitory effect on the growth of Staph. aureus bacteria. All concentrations of the ethanolic extract of Moringa oleifera leaves had a significant inhibitory effect on the growth of Staph. aureus bacteria. The effect increases with the increase of the used concentration, as the diameter reached a maximum of 16.17 mm at a concentration of 100 mg ml-1. Moringa oleifera leaf extract did not have an inhibitory effect on the growth of Klebsiella pneumoniae bacteria at all extract concentrations.